Demi-flexible operating policies to promote the performance of public transit in low-demand areas. (October 2015) - Qiu, Feng; Shen, Jinxing; Zhang, Xuechi; An, Chengchuan
Highlights: We propose a novel concept named demi-flexible transit operating policies. Analytic models are developed to reproduce transit operation. The system performance is evaluated at expected and unexpected demand levels. Experiments demonstrate the unique advantages of demi-flexible operating policies. Abstract: The efforts of providing attractive transport service to residents in sparse communities have previously focused on operating flexible transit services. This paper identifies a new category of transit policies, called demi-flexible operating policies, to fill the gap between flexible transit services and conventional fixed-route systems. The passenger cost function is defined as the performance measure of transit systems and the analytic work is performed based on a real-world flag-stop transit service, in which we compare its system performance with another two comparable systems, the fixed-route and flex-route services, at expected and unexpected demand levels in order to be closer to reality. In addition, the dynamic-station policy is introduced to assist the flex-route service to better deal with unexpectedly high demand. Experiments demonstrate the unique advantages of demi-flexible operating policies in providing affordable, efficient, and reliable transport service in low-demand operating environments and this work is helpful to optimize the unifying framework for designing public transit in suburban and rural areas.